Magnetic and conventional shape memory behavior of Mn-Ni-Sn and Mn-Ni-Sn(Fe) alloys - Turabi, A. S.; Lazpita, P.; Sasmaz, M.; Karaca, H. E.; Chernenko, V. A. (Iop Publishing Ltd, 2016)
Magnetic and conventional shape memory properties of Mn49Ni42Sn9(at.%) and Mn49Ni39Sn9Fe3(at.%) polycrystalline alloys exhibiting martensitic transformation from ferromagnetic austenite into weakly magnetic martensite are characterized under compressive stress and magnetic field. Magnetization difference between transforming phases drastically increases, while transformation temperature decreases with the addition of Fe. Both Mn49Ni42Sn9 and Mn49Ni39Sn9Fe3 alloys show remarkable superelastic and shape memory properties with recoverable strain of 4% and 3.5% under compression at room temperature, respectively. These characteristics can be counted as extraordinary among the polycrystalline NiMn-based magnetic shape memory alloys. Critical stress for phase transformation was increased by 34 MPa in Mn49Ni39Sn9Fe3 and 21 MPa in Mn49Ni42Sn9 at 9 T, which can be qualitatively understood in terms of thermodynamic Clausius-Clapeyron relationships and in the framework of the suggested physical concept of a volume magnetostress.
Keywords: Mn-Ni-Sn(Fe) metamagnetic shape memory alloys; martensitic transformation; shape memory; superelasticity; volume magnetostress